Didactical characteristics of Dutch websites about kidney transplantation targeted for kidney patients and living donors: An exploratory study - Charlotte W. van Klaveren; Peter G.M. de Jong; Renée A. Hendriks; Franka Luk; Aiko P.J. de Vries; Paul J.M. van der Boog; A.J. Rabelink; Marlies E.J. Reinders (PEC Innovation, 2022)
Objective: The aim was to explore the origin, content topics, teaching modes (instruction, interaction, and assessment), and corresponding social-epistemological dimensions (choices in knowledge transfer vs. knowledge building, and individual vs. group learning) of web-based information on kidney transplantation targeted for patients and living donors. Methods: Dutch websites on kidney transplantation were retrieved using the search engine Google.nl. From 24 websites, 250 webpages were examined on origin, content topics, teaching modes, and corresponding social-epistemological dimensions. Results: The majority of the websites had a professional organization as origin (20/24). The number and distribution of content topics varied among the websites. Of the 16 different teaching modes found, 11 were instructional, 4 were interactional, and 1 assessment mode was found. The websites offered almost exclusively teaching modes on individual and passive learning, whereas group learning and interactive knowledge building was hardly encountered. Conclusion: The diversity in teaching modes and social-epistemological dimensions of Dutch websites on kidney transplantation targeted for patients and living donors is limited. The websites only provided a partial view on kidney transplantation; information regarding contact with others, e.g. support, was limited. A more balanced availability of teaching approaches and content topics is desirable to fit with the didactical goals to make well-considered health decisions.